IN VITRO INDUCTION OF CALLUS FROM EXPLANTS OF Capsicum annum L. - Castillo Zavala, José (2022)
Capsicum annuum L. is of importance in world cuisine and its cultivation is susceptible to different pests and diseases, so its reproduction in plant tissues turns out to be the best alternative for its large-scale production of its good quality derivatives, and therefore suitable, for the international market. In this sense, calluses can be induce in vitro from explants of C. annuum. For this, the sterilization and germination of the seeds of this species was carried out in MS medium (Murashigue-Skoog), then the dedifferentiation of the explants, using this medium, supplemented with 2.4 D and Kinetin. Desdifferentiation of C. annuum explants was found at the second week of culture, followed by subsequent callus formation at the fourth and fifth week of the experiment. It is concluded that these processes carried out were produced mainly by auxins and cytokinins added to the medium.